LITERATURE REVIEW ON INQUIRY APPROACHES IN EDUCATION - veranica ayu utari (Teaching and General Education Studies, 2026)
Learning approaches play a crucial role in determining the success of the educational process. One approach frequently used in learning activities is the inquiry approach, which emphasizes investigative activities for students to independently acquire knowledge. This article aims to review various literature related to the concept, advantages, disadvantages, and application of the inquiry approach in learning. The method used in writing this article is a literature study, examining various sources such as books and scientific journals relevant to the research topic. The results of the study indicate that the inquiry approach can increase student activeness in the learning process, develop critical thinking skills, deepen conceptual understanding, and increase learning motivation. However, the implementation of this approach also has several limitations, including requiring relatively longer learning time, requiring teachers to be prepared in designing learning activities, and presenting difficulties for some students who are not accustomed to independent learning. Based on these results, it can be concluded that the inquiry approach is an effective learning approach for creating an active and meaningful learning process. Therefore, this approach can be used as an alternative in efforts to improve the quality of learning in schools.